Effect of Moisture Level of Grapes Germplasm on Its Viability After Using Different Methods and Terms of Hypothermic Storage - Prystalov, Anton I. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):181.